Implementasi PjBL Terintegrasi KSE untuk Meningkatkan Keaktifan dan Hasil Belajar Peserta Didik pada Pembelajaran Matematika Kelas V SD - Ika Desy Ramayati; Ninik Srijani; Patuh Muhajir (Edukasi Elita : Jurnal Inovasi Pendidikan, 2025)
This research aimed to improve students’ activities and learning outcomes of Mathematics in solving problems related to money on chapter whole numbers up to 100.000 by using project-based learning integrated with social emotional learning (SEL) for students at class 5 in SDN Pilangrejo 02. This research used classroom action research which carried out in 2 cycles. Each cycle was carried out in 4 stages, includes planning, action, observation, and reflection. This research used observation, tests and documentation as the instruments. The data analysis used qualitative and quantitative descriptive analysis. The result of this study showed the percentage of students’ activity in cycle I reached 58.84% and increased 87.23% in cycle II. The percentage of learning outcomes in pre-test (pre-cycle) reached 27.28% with average score of 60, it increased 72.23% with average score of 80 in post-test (cycle I), and increased to 90% with average score of 93 in post-test (cycle II). So, it concluded that the implementation of Project Based Learning integrated with Social Emotional Learning (SEL) can improve the students’ activities and learning outcomes of mathematics subjects at class 5 in SDN Pilangrejo 02.